Strategies of Capital Accumulation in Times of Land Scarcity. A Field Perspective on Social Housing Construction in Vienna - Carina Altreiter; Katharina Litschauer (Johannes Kepler University Linz, Research Project SPACE - Spatial Competition and Economic Policies, 2021)
The social housing market in Vienna is known for its large, decommodified housing stock and therefore has been subject to extensive research. However, current approaches lack a nuanced account of the main producers of social housing today, namely limited-profit housing associations. Following Bourdieu, this paper applies a field perspective to grasp the configuration and distribution of different capital forms within the social housing market. It explores how field positions influence possibilities for acquiring building plots, something that has become increasingly difficult in recent years due to rising market prices and increasing competition for land distributed by the municipality of Vienna via 'developer competition' proceedings. Drawing on multiple correspondence analysis and qualitative interviews, the article shows that despite economic capital remaining a pivotal currency in the field, the involvement of the municipality adds more weight to specific forms of cultural and social capital compared to economic capital.
Keywords: L1; L32; R31; 330; social housing market; scarcity; field theory; cultural capital; capital accumulation